Knowledge, Attitudes and Practices of Inhabitants of Eastern Democratic Republic of the Congo on The Ongoing Ebola - Kamabu, Larrey Kasereka; Best, Fidèle Lungu; Kasusula, Bienvenu Muhindo; Manzekele, Mathieu Katembo; Butala, Eric Sadiki; Kambere, Thaddée Katembo (The Lancet Public Health, 2020)
Despite the control strategies instituted for 21 months, the revival of old homes after a period of lull is becoming more and more worrying. The objectives of this study were to assess Knowledge, Attitudes, Practices (KAP) and to identify the factors influencing the KAP of the inhabitants of eastern DRC on EVD. We used a cross-sectional descriptive study. Data analysis was carried out in SPSS 16.0 for windows(SPSS). Statistical analysis mainly used frequencies, proportions and means on the descriptive level. The Pearson correlation coefficient r, the student t test and ANOVA were used to test the relationship and the difference between the variables and the groups at the 0.05 threshold. It emerges from this study that most heads of households had good knowledge, attitudes and practices on EVD with the respective general averages of: (0.7354 ± 0.21007), (2.3921 ± 0.27009) and (2, 4841 ± 0.47438). The likely factors for the sustainability of EVD identified were the factors of self- esteem in playing a role in EVD prevention and management and self-efficacy, negligence and lack of awareness with the respective averages (M = 1.7966 ± 0.76861), (2.5508 ± 0.45787) and (2.2542 ± 0.65615). The lack of self-esteem, negligence, and insufficient awareness have been identified as determinants of KAP. These results incite to change strategies of the response and organize training and information sessions for the masses on EVD focused on these factors identified above.
Keywords: KAP; Investigation; War-torn; Inhabitants